PERKEMBANGAN AWAL ISLAM DI NUSANTARA DAN WACANA SUFISTIK TASAWUF FALSAFI PADA ABAD 17 - Arki Auliahadi; Ariska Oktavia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Since the beginning of the archipelago, the archipelago has functioned as a cross-trade route for the West Asian, East Asian and South Asian regions. The arrival of Islam in the archipelago is full of debates, there are three main issues that historians debate. First, the place of origin of Islam. Second, the carriers. Third, the time of arrival. However, Islam has entered, grown and developed in the archipelago quite rapidly. Considering the arrival of Islam to the archipelago which at that time already had Hindu-Buddhist culture. So this is very encouraging because Islam is able to develop in the midst of the lives of people who already have strong and longstanding cultural roots. The arrival of Islam to the archipelago experienced various ways and dynamics, including trade, marriage, social culture, and so on. This causes the growth and development of Islam in this region has its own style. In addition, Ulama who came to the Nusantara region approached their people with an approach that tended to be gentle. In this case it is done with a philosophical approach to Sufism. This teaching is easily accepted and experiences rapid development in the midst of the Nusantara community so that Islam is more easily accepted. This paper uses a historical approach that emphasizes the aspects of time and chronology by using a heuristic approach, source criticism, synthesis and historiography which are characteristic of the final results of writing history.